Chemical constituents from the calyces of Hibiscus Sabdariffa Linn and its a-Glucosidase inhibitory activity - Nadzirah Mohd Jauah (Tanjong Malim, 2018)
Chemical constituents from the calyces of Hibiscus Sabdariffa Linn and its a-Glucosidase inhibitory activity by Nadzirah Mohd Jauah